P65 Quality of inpatient care for copd exacerbations and it's impact on clinical outcomes. (15th November 2017) - Cushen, B; Alsaid, A; Cleere, E; MacHale, P; Tompkins, L; Sulaiman, I; Greene, G; MacHale, E; Costello, RW
Abstract : High rates of rehospitalisation in the 90 days following COPD exacerbation are a concern internationally due to their unpredictable nature, the impact on patient's health and the pressures they pose on healthcare systems. Strategies to reduce rehospitalisation have looked to improve inpatient management at the time of the index admission. We assessed the rate of adherence to international acute COPD management guidelines and examined which components of these guidelines have the greatest impact on clinical outcomes. Data from 208 patients hospitalised with an acute exacerbation of COPD was retrospectively collected from the medical chart. Adherence to five key components of COPD management was assessed. These included 1) Arterial blood gas measurement, 2) Administration of Controlled Oxygen therapy, 3) Regular short-acting bronchodilator therapy, 4) Prescription of systemic steroids (oral if suitable) and 5) Prescription of appropriate antibiotics, where applicable. Hospital length of stay(LOS) and readmissions up to 90 days following discharge were recorded. The mean age was 71 years and the majority were female. The mean FEV1 was 48% predicted and the median DECAF score was 1 (2) suggesting a low risk exacerbation. Almost 50% had a co-existent consolidation on chest radiograph. The median LOS was 8 days; 80% were discharged directly to home. In the majority of cases only 3 of the 5 acute management components were completed. More than 90% of patients received antibiotics but only one-third were prescribed guideline-directed therapy. Intravenous steroids were used in the majority of cases, 67%, in preference to oral steroids. On multivariate linear regression analysis adjusting for exacerbation severity, age, FEV1 and discharge destination, appropriate prescription of oral steroid therapy reduced LOS by 1.3 days, p=0.023. By day 90, 38% of patients had been readmitted to hospital. The probability of readmission was decreased in those who had received guideline-directed antibiotic therapy, OR 0.35 (95% CI 0.15–0.79) p=0.012. Adherence to acute COPD management guidelines is suboptimal. The greatest improvements in clinical outcomes were associated with prescription of oral steroids, where applicable, and guideline-directed selection of antibiotic therapy. These components should, therefore, be a focus of strategies to improve quality of inpatient care in COPD.